Preclinical Validation of a Novel Device Designed to Reduce Biofilms on Percutaneous Osseointegrated Abutments. Issue 8 (September 2019) - Sammons, Rachel; East, Matthew; Grant, Melissa; Proops, David
Abstract : Aim: To assess the efficacy of a prototype cleaning device in removing biofilm from skin-penetrating abutments. Background: Adverse skin reactions around percutaneous osseointegrated implants have been linked to poor hygiene and infection. A cleaning device made from open-cell polyfoam has been developed to facilitate manual cleaning of abutments by the patient. Methods: Serratia biofilm was grown on clean and sterile conical bone-anchored hearing system abutments including both pre-2007 (straight sided) and post-2007 (conical-sided) designs. Eighteen were photographed and then subjected to cleaning using a toothbrush or the cleaning device soaked in water or a proprietary mouthwash. Biofilm on a further group of 10 conical abutments was recorded using a scanning electron microscope before and after cleaning with the test device soaked in water. Quantitative analysis of the efficiency of the cleaning was made using image analysis. Results: Removal of biofilm using a dry or wet toothbrush was not as effective as cleaning with the device. In 10 cases subjected to image analysis, approximately 90% of the biofilm was removed from the top third of the abutments, 85% from the middle third, and 48% from the basal third. Conclusion: The cleaning device is effective in removing most biofilm from the test abutments and represents a significant improvement in comparison with traditional methods such as a toothbrush.